Some Outcomes on Fuzzy Menger Space via Common Property (E.A) and Absorbing Maps - Satyanna, K.; Srinivas, V.; R., Umamaheshwar Rao (Communications in Mathematics and Applications, 2024)
The present idea of this paper is to generalize the result proved by Sing et al. (Fixed point results in Fuzzy Menger space, Journal of Applied Mathematics and Bioinformatics 5 (2015), 67 – 75) obtaining two results in fuzzy Menger space by employing absorbing maps, common property (E.A) and occasionally weakly compatible mappings. Moreover, these results are justified by suitable examples.